Myeloid Colony-Stimulating Factors as Regulators of Macrophage Polarization - Hamilton, Thomas A.; Zhao, Chenyang; Pavicic, Paul G.; Datta, Shyamasree (Frontiers in Immunology, 2014)
The scope of functional heterogeneity in macrophages has been defined by two polarized end states known as M1 and M2, which exhibit the pro-inflammatory activities necessary for host defense and the tissue repair activities required for tissue repair respectively. Macrophage populations in different tissue locations exist in distinct phenotypic states across this M1/M2 spectrum and the development and abundance of individual subsets result from the local and systemic action of myeloid colony stimulating factors (CSFs) including M-CSF and GM-CSF. These factors have relatively non-overlapping roles in the differentiation and maintenance of specific macrophage subsets. Furthermore there is now evidence that CSFs may also regulate macrophage phenotype during challenge. Cell culture studies from multiple laboratories demonstrate that macrophages developed in the presence of GM-CSF exhibit amplified response to M1 polarizing stimuli while M-CSF potentiates responses to M2 stimuli. As a consequence these factors can be important determinants of the magnitude and duration of both acute and chronic inflammatory pathology and may, therefore, be potential targets for therapeutic manipulation in specific human disease settings.